2019
DOI: 10.1071/ah17032
|View full text |Cite
|
Sign up to set email alerts
|

Aging in Australia: country of birth and language preferences of residents in aged care facilities

Abstract: There is a need to better understand the use of aged care services by people from culturally and linguistically diverse backgrounds. The aim of the present study was to describe the prevalence of people living in residential aged care facilities (RACFs) who were born in non-English-speaking countries and/or have a preferred language other than English and to describe service utilisation rates. The present study consisted of a secondary analysis of data from the Australian Institute of Health and Welfare Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Very old individuals are the ones who need supportive care services as they are nearing the end of life and this is also at a time of life when spousal death and the death of others who could be their first line of care [23]. We also found that a lower proportion of people entering PRAC were born in non-English speaking countries (< 20%) and had a preferred language (< 12%) other than English (Culturally And Linguistically Diverse, CALD), which had been reported by AIHW for the national cohort and studies by Petrov et al and Jorgensen et al [4, 11, 24]. When compared to Australian general population (about 21% spoke a language other than English), the proportion of older CALD people using PRAC was low [25].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Very old individuals are the ones who need supportive care services as they are nearing the end of life and this is also at a time of life when spousal death and the death of others who could be their first line of care [23]. We also found that a lower proportion of people entering PRAC were born in non-English speaking countries (< 20%) and had a preferred language (< 12%) other than English (Culturally And Linguistically Diverse, CALD), which had been reported by AIHW for the national cohort and studies by Petrov et al and Jorgensen et al [4, 11, 24]. When compared to Australian general population (about 21% spoke a language other than English), the proportion of older CALD people using PRAC was low [25].…”
Section: Discussionsupporting
confidence: 73%
“…Currently 7% of those over 65 years of age are receiving residential aged care services [3]. This group are also heavy users of health services accounting for a significant proportion (41%) of all hospitalisations and days spent in hospital (48%) [4]. In 2015–16 the Australian government spent $17 billion dollars on aged care services, with over two thirds of this spending allocated to residential aged care services, and this expenditure is expected to rise significantly over the coming decades [5].…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to understand the diversity of aged care residents who prefer to speak a language other than English. In so doing, it expands on a 2019 study by Petrov et al 18 describing linguistic diversity in aged care. The specific questions addressed in this study are as follows:…”
Section: Introductionmentioning
confidence: 69%
“…The current 80 languages preferred by RAC residents born in a NMESC is a slight increase on the 70 languages reported by Petrov et al in 2019. 18 Of the 80 languages identified in the current study, approximately 60 have fewer than 150 speakers Australiawide. Residents speaking these languages may be isolated as one of the few or only speakers of their language in their facility.…”
Section: Discussionmentioning
confidence: 88%
“…In Australia, people ≥ 65 years old are major users of health services, constituting a large proportion of total hospitalisations (41%), days spent in hospitals (48%), and other primary and secondary health care services. [ 4 , 5 ]. As part of these services, timely radiology is key in allowing for early treatment and the best possible care.…”
Section: Introductionmentioning
confidence: 99%